VENTURE CAPITAL AND PRIVATE EQUITY IN CHINA: MARKET DEVELOPMENT AND VENTURE CAPITAL LIFE-CYCLE - Wang, Lu (2005)
The venture capital and private equity industry has significantly developed in China since 1980s. However, as one of the world's fastest growing economies and is home to 1.3 billion population, the examination of venture capital and private equity in China are very limited. This study leverages Wright et al. well-structured conceptual framework and life-cycle model to explore China's entire venture capital and private equity industry climate and to examine the individual venture capital and private equity activities. Based on the domestic and foreign VC/PE investors' interviews, the article discusses the impact and indication of the findings from four macro aspects and investment life-cycle perspectives respectively.